2019
DOI: 10.4314/tjpr.v17i12.14
|View full text |Cite
|
Sign up to set email alerts
|

Pumilaside A from Litchi semen induces apoptosis in human gastric cancer BGC823 cells via activation of death receptor- and mitochondria-mediated apoptotic pathways

Abstract: Purpose: To investigate the cytotoxic effect of pumilaside A from Litchi semen against human gastric cancer BGC823 cells, and unravel its possible mechanism(s) of action. Methods: The cytotoxic activity of pumilaside A (5-40 μg/mL) against BGC823 cells was assessed by thiazolyl blue tetrazolium bromide assay. The pro-apoptotic effect of PA (10, 20 or 40 μg/mL) on BGC823 cells was monitored by flow cytometry, while the mechanisms involved were investigated using western blot. Results: Pumilaside A significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…In Figure S1C, the MS/MS spectrum of m/z 417.2493 [M‐H] − from compound 34, whose possible elemental composition is C 21 H 38 O 8 , showed four major fragment ions at m/z 385.1922 [M‐H‐CH 4 O] − , 255.1955 [M‐H‐C 6 H 10 O 5 ] − , 179.1501 [M‐H‐C 15 H 26 O 2 ] − , and 161.0430 [M‐H‐C 15 H 26 O 2 ‐H 2 O] − ; 179.1501 [M‐H‐C 15 H 26 O 2 ] − of compound 34 was thought to be a glucose moiety, followed by 161.0430 [M‐H‐C 15 H 26 O 2 ‐H 2 O] − which was thought to further lose a hydroxyl moiety; 255.1955 [M‐H‐C 6 H 10 O 5 ] − was hypothesized to be the glycoside portion of compound 34, and consulting the literature it may be a eudesmane‐type sesquiterpenoid moiety, with 385.1922 [M‐H‐CH 4 O] − further confirming the position of the methanol group on the sesquiterpene. Thus, compound 34 was considered to be pumilaside A (Zheng et al, 2018), which was also first identified in CTS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure S1C, the MS/MS spectrum of m/z 417.2493 [M‐H] − from compound 34, whose possible elemental composition is C 21 H 38 O 8 , showed four major fragment ions at m/z 385.1922 [M‐H‐CH 4 O] − , 255.1955 [M‐H‐C 6 H 10 O 5 ] − , 179.1501 [M‐H‐C 15 H 26 O 2 ] − , and 161.0430 [M‐H‐C 15 H 26 O 2 ‐H 2 O] − ; 179.1501 [M‐H‐C 15 H 26 O 2 ] − of compound 34 was thought to be a glucose moiety, followed by 161.0430 [M‐H‐C 15 H 26 O 2 ‐H 2 O] − which was thought to further lose a hydroxyl moiety; 255.1955 [M‐H‐C 6 H 10 O 5 ] − was hypothesized to be the glycoside portion of compound 34, and consulting the literature it may be a eudesmane‐type sesquiterpenoid moiety, with 385.1922 [M‐H‐CH 4 O] − further confirming the position of the methanol group on the sesquiterpene. Thus, compound 34 was considered to be pumilaside A (Zheng et al, 2018), which was also first identified in CTS.…”
Section: Resultsmentioning
confidence: 99%
“…For compound 19 in Figure S1B anol group on the sesquiterpene. Thus, compound 34 was considered to be pumilaside A (Zheng et al, 2018), which was also first identified in CTS. À was considered to be the glycoside portion of compound 40, which may be an ester according to the matching results between the fragment information and the…”
Section: The Chemical Profile and Compound Identificationmentioning
confidence: 99%
“…found the same compound in Ficus pumila fruit and determined its structure as pumilaside A [16]. Hence, compound (2) was tentatively assigned as pumilaside A. Pumilaside A was also identified in Litchi semen and Artemisia vulgaris [17,18]. In conclusion, from the alcohol extract of P. micrantha's rhizomes, analyzed by ESI-QTOF negative and positive modes, and APCI-QTOF positive mode, one known compound of glycoside J-3 isolated in the Peliosanthes sinica and three known compounds, namely pumilaside A, pumilaside C, and β-sitosterol previously undescribed in the Peliosanthes genus were tentatively identified.…”
Section: Uhplc-q-tof Analysismentioning
confidence: 88%